Assessment of genetic variability and diversity for lodging resistance and yield related traits in rice germplasm (Oryza sativa L.) - MV, Rama Sai; Chintala, Dr.Sreelakshmi; M, Shanthi Priya; U, Vineetha; Vemireddy, Lakshminarayana R; M, Reddisekhar (ORYZA-An International Journal of Rice, 2025)
Genetic variability and diversity studies were conducted for five lodging resistance traits and ten grain yield-related traits in 104 rice germplasm lines. The results revealed that PCV values were slightly higher than GCV values, indicating the influence of the environment on trait expression. Heritability coupled with high genetic advance was observed for plant height, number of panicles per plant, panicle weight, number of grains per panicle, test weight, and grain yield, which indicates predominant additive gene action. Correlation analysis revealed a significant correlation between lodging resistance traits such as culm diameter, culm thickness, section modulus, and bending moment, and yield-related traits, namely number of panicles, panicle weight, and grain yield. Path coefficient analysis showed that bending moment, panicle weight, and days to 50% flowering exhibited the highest direct effects on grain yield. Culm thickness and culm diameter recorded negative indirect effects on grain yield. According to Mahalanobis D², the genotypes were divided into six clusters. Cluster I had the highest number of rice genotypes (83), followed by Clusters II and III with ten and eight genotypes, respectively. Clusters IV, V, and VI were mono-genotypic. The inter-cluster distance between Clusters V and VI was the maximum. Cluster III also exhibited a higher intra-cluster distance. Further, Cluster IV recorded the highest values for most of the lodging and yield-related traits. Cluster V recorded the lowest mean for days to 50% flowering and days to maturity.